COMMON GOOD: A Moral Category in the Social Thought of John Paul II - Britto, Richard (Journal of Dharma, 2010)
John Paul II, by his pontificate of twenty six years (1978-2005), has left behind an enormous legacy, with profound significance for the Church and for the world. He deserves much respect not just as a spiritual leader but as a moral and world leader as well. As a professional philosopher and a theologian, he raised the consciousness of all human beings of his age about the truth of human life and its destiny. As an ethicist, a universal pastor and a world leader, he was committed to the cause of the promotion of human rights and the common good. In an era of history dominated by totalitarian communism, individualistic capitalism, relativism and post-modernism, which posed a threat to human freedom, moral culture, religion and humanism, he constantly defended the dignity of human life.